2001
DOI: 10.5006/1.3290342
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the Chemistry and Electrochemistry in Cracks—A Review

Abstract: The state of the art in crack chemistry modeling is assessed. An overview of conceptual understanding of the processes occurring in a crack is given, and the foundations for establishing mathematical equations for the mass conservation of species in a crack are described. With the exception of concentrated solutions, crack chemistry modeling is at the stage where the primary uncertainty in prediction should be associated only with the paucity of data for the input parameters. Establishing an electrochemical da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 18 publications
2
42
0
1
Order By: Relevance
“…In aqueous environments, the external chemical potential may vary along the crack flanks. For instance, hydrolysis of highly concentrated metal ions generates a localized acidified medium [12,42], giving an enhanced source of hydrogen. However, Sharland and Tasker [43] have shown that such variations are negligible up to very small distances from the crack mouth.…”
Section: Philosophical Magazine 2945mentioning
confidence: 99%
See 1 more Smart Citation
“…In aqueous environments, the external chemical potential may vary along the crack flanks. For instance, hydrolysis of highly concentrated metal ions generates a localized acidified medium [12,42], giving an enhanced source of hydrogen. However, Sharland and Tasker [43] have shown that such variations are negligible up to very small distances from the crack mouth.…”
Section: Philosophical Magazine 2945mentioning
confidence: 99%
“…These boundary conditions may in turn be related to transport in the crack environment and reactions at the crack surfaces [11,12]. Atomic hydrogen, being the smallest possible impurity, is generally considered to be transported easily by a combination of interstitial and intergranular diffusion [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Par ailleurs, les similitudes observées dans de nombreux cas, tant en terme d'accélération de la propagation que de mécanismes de rupture, entre les solutions aqueuses et les atmosphères gazeuses, pour lesquelles il n'a pas d'électrolyte présent en pointe, suggèrent que ce sont les processus liés à l'hydrogène généré par les réactions électrochimiques qui sont prédominants suivant des mécanismes (HELP ou HEDE) qui restent là encore à préciser. Ainsi Ro et al [71,72] montrent, dans le cas d'alliages Al-Cu-Li-Mg/Li ayant une propension à développer des modes de propagation fortement cristallographiques sous environnement inerte conduisant à la formation de facettes proches de {111}, que l'air ambiant comme une solution 3.5% NaCl ne conduisent plus à la formation de ce type de facettes mais engendre un changement marqué des surfaces de rupture, ce qu'un modèle deLa chimie et composition de la solution au voisinage d'une fissure constituent donc un nouveau domaine d'étude à part entière [74,76,77]. Deux points essentiels ressortent: le milieu est généralement plus acide en pointe de fissure car les conditions électrochimiques sont très productrices d'hydrogène, et la solution peut se désaérer du fait d'un apport d'oxygène limité.…”
Section: Quelques Spécificités De La Fatigue En Milieu Aqueuxunclassified
“…No evidence of hydrogen trapping was found at grain boundaries in either the pure aluminium or the Al-Zn-Mg alloy. According to first-principle calculations done by Lu & Kaxiras [35], a large amount of H atoms (up to 12) can be trapped at a single vacancy, which overcompensates the energy cost to form the vacancy defect. Therefore, current work only considers hydrogen trapping at dislocations and vacancies.…”
Section: (C) Hydrogen Transportmentioning
confidence: 99%
“…It is known that SIT is valid up to ionic strength of 3.5 mol kg −1 . The general SIT equation for a single ion, i, can be written as 12) where D, the Debye-Hückel term, equals…”
Section: (B) Crack Chemistry (I) Governing Equationsmentioning
confidence: 99%